2015
DOI: 10.18483/ijsci.733
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Weather Parameters and Female Mosquito Abundance and Distribution in Makurdi - a Mosquito Infested Area in North Central Nigeria

Abstract: The relationship between weather parameters and female mosquito populations/distribution were determined in Makurdi from four localities over a 12-month period. Data on temperature, rainfall and relative humidity were obtained using the expertise of the Nigerian Meteorological Agency at the Tactical Air Command headquarters in Makurdi. Adult female mosquitoes (4,320), comprising anophelines and culicines were caught indoors and identified using standard keys and procedures. 1,040 (24.1%) were Anopheles gambiae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
1
6
2
Order By: Relevance
“…This research work investigated the sporozoites infection rate of infected female Anopheles mosquitoes in Gombe south LGAs, Gombe State, northeastern Nigeria. A total of 1,860 female Anopheles were dissected, out of which 665(35.8%) sporozoites infection rate was observed as the overall in the four LGAs, the outcome of this research concur with the findings of (Salum et al, 2021;Oduola et al, 2021;Manyi et al, 2014;Najila et al, 2019) where in separate studies form Kilombero velleys, southeastern Tanzania, Kwara state and Markurdi in north-central Nigeria respectively, but differs with the reports of (Lamogo et al, 2019;Maia et al, 2019;Obembe and Awopetu, 2014). from some selected communities in Shongom LGA, Gombe state, and Sri Lanka, the difference in the results could be as a result of geographical factors variation such as: the amount of rainfall received in the site, temperature, and availability of potential breeding sites of the vectors, the size of communities covered and other factors like conduciveness of environments for the Anopheles mosquito to live comfortably.…”
Section: Discussionsupporting
confidence: 82%
“…This research work investigated the sporozoites infection rate of infected female Anopheles mosquitoes in Gombe south LGAs, Gombe State, northeastern Nigeria. A total of 1,860 female Anopheles were dissected, out of which 665(35.8%) sporozoites infection rate was observed as the overall in the four LGAs, the outcome of this research concur with the findings of (Salum et al, 2021;Oduola et al, 2021;Manyi et al, 2014;Najila et al, 2019) where in separate studies form Kilombero velleys, southeastern Tanzania, Kwara state and Markurdi in north-central Nigeria respectively, but differs with the reports of (Lamogo et al, 2019;Maia et al, 2019;Obembe and Awopetu, 2014). from some selected communities in Shongom LGA, Gombe state, and Sri Lanka, the difference in the results could be as a result of geographical factors variation such as: the amount of rainfall received in the site, temperature, and availability of potential breeding sites of the vectors, the size of communities covered and other factors like conduciveness of environments for the Anopheles mosquito to live comfortably.…”
Section: Discussionsupporting
confidence: 82%
“…Torn nettings on windows and the absence of mosquito-treated nets allowed these vectors into the wards. The abundance of mosquitoes during the rainy season was also established by investigations in Bayelsa State and other ecological zones [24][25][26][27][28][29]. However, okorie et al observed a decline in mosquito abundance during the rainy season [23].…”
Section: Discussionmentioning
confidence: 99%
“…The female Anopheles mosquito transmits malaria parasites, Aedes aegygti mosquitoes are known to transmit yellow fever and dengue fever. Anopheles and Culex species have also been incriminated in transmitting lymphatic filariasis [14].…”
Section: Introductionmentioning
confidence: 99%